Exposure to "Exergames" Increases Older Adults' Perception of the Usefulness of Technology for Improving Health and Physical Activity: A Pilot Study - Bird, Marie-Louise; Clark, Brodie; Millar, Johanna; Whetton, Sue; Smith, Stuart (JMIR Publications, 2015)
BackgroundHigh rates of sedentary behaviors in older adults can lead to poor health outcomes. However, new technologies, namely exercise-based videogames ("exergames"), may provide ways of stimulating uptake and ongoing participation in physical activities. Older adults' perceptions of the use of technology to improve health are not known. ObjectiveThe study aimed to determine use and perceptions of technology before and after using a 5-week exergame. MethodsFocus groups determined habitual use of technology and the participant's perceptions of technology to assist with health and physical activity. Surveys were developed to quantitatively measure these perceptions and were administered before and after a 5-week intervention. The intervention was an exergame that focused on postural balance ("Your Shape Fitness Evolved 2012"). Games scores, rates of game participation, and enjoyment were also recorded. ResultsA total of 24 healthy participants aged between 55 and 82 years (mean 70, SD 6 years) indicated that after the intervention there was an increased awareness that technology (in the form of exergames) can assist with maintaining physical activity (P<.001). High levels of enjoyment (Physical Activity Enjoyment Scale [PACES-8] score mean 53.0, SE 0.7) and participation rates over the whole study (83%-100%) were recorded. ConclusionsOlder adults' have low perception of the use of technology for improving health outcomes until after exposure to exergames. Technology, in the form of enjoyable exergames, may be useful for improving participation in physical activity that is relevant for older adults.